Formation of management model for assessment the economic security of individual interests - P. A. Ilyin (Управленческие науки)
In the conditions of reformatting and transformation of the world economy, as well as the aggravation of the international situation, there is an objective need to form a model for assessing the economic security of an individual, taking into account both economic factors and other aspects of social life.As the object of article, the author considers relationships that influence the economic security of vital interests of the individual. The subject is indicators of its condition and performance on which its survival and sustainability depend, and tasks are to study the raw data for their formation. The aim of the article is to develop a model of economic security of the individual.As a result, the author has formed a model of assessment of economic security of the person, which takes into account assessment of income, expenses, debt, property, family, education, as well as environmental impact, that is, not only its financial and economic situation, but also socio-cultural traits. The relevance of the study, conducted using logical and mathematical methods is due to the possibility of applying its results for the rapid identification of places of social tension and the adoption of the necessary measures, and to obtain information on the presence or absence of threats to a particular person’s economic security in order to make certain management decisions.